A novel PCM and TCE based thermal management of battery module. (1st March 2022) - Ambekar, Shivam; Rath, Prasenjit; Bhattacharya, Anirban
Highlights: A novel PCM-Fin arrangement is proposed for thermal management of battery module. Phase change within PCM is modelled using source based implicit enthalpy method. Three different discharge rates are studied with 1C charging for multiple cycles. FS-3 is found to be the best configuration for the present study. Abstract: This paper presents a novel combination of Phase Change Material (PCM) and fins as Thermal Conductivity Enhancer (TCE) for effective thermal management of battery module. A numerical study of the battery module thermal management system using PCM and internal fins for maintaining the battery temperature below the safe limit of 60 °C for more than one cycle is carried out. Both joule and entropic heat generation is considered for more generality in line with the actual case. An implicit finite volume based numerical methodology is used to solve the governing energy transport equation. Phase change in PCM is modelled using the implicit source based enthalpy method. A two-dimensional model is developed to study the thermal performance of battery module with 4S4P cell structure (16 cells) with PCM filled in between the cells. To improve the heat dissipation more effectively from PCM, metal fins as TCE are inserted in the space filled with PCM. Five fin structures with fin arrangement parallel to the boundary and tilted at an angle of 45 ° to the boundary are developed and studied to find the best configuration for effective transport of heat from the system to the boundaries and subsequent convection away to the ambient. Results shows more uniformity in temperature distribution within the battery module for better thermal performance for longer period of operation. Using fins embedded in PCM, the battery module temperature is maintained below 60 °C even after two and half discharge–charge cycle of 2C and 3C discharge rates where FS-3 structure is proved to be most efficient.